Remedial physical culture as a component of physical rehabilitation with osteochondrosis of the lumbarsacral spine - Pasichnyk V.M (Kharkov National Pedagogical University, 2010)
The analysis of application of medical physical culture is resulted in a physical rehabilitation at the osteochondrosis of the lumbosacral spine. Reasons of origin and clinical displays of disease are examined. The mechanism of medical influence of physical exercises and description of the motive modes is lighted up. Exercises are neat taking into account the period of disease, by the features of his flowing and functional state of patient. It is marked that the increasing trained provides an organism adaptation to loadings and results in liquidation of violations.